2019
DOI: 10.1177/1179573519831997
|View full text |Cite
|
Sign up to set email alerts
|

Daily Practice Managing Resistant Multiple Sclerosis Spasticity With Delta-9-Tetrahydrocannabinol: Cannabidiol Oromucosal Spray: A Systematic Review of Observational Studies

Abstract: Background/purpose:Spasticity is one of the most common symptoms in people with multiple sclerosis (MS). Conventional anti-spasticity agents have limitations in their efficacy and tolerability. Delta-9-tetrahydrocannabinol: cannabidiol (THC:CBD) spray, a cannabinoid-based medicine, is approved as an add-on therapy for MS spasticity not adequately controlled by other anti-spasticity medications. The results from randomized controlled trials (RCTs) have demonstrated a reduction in the severity of spasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Data obtained from these studies confirmed CBD's anti-seizure properties along with a good tolerance profile. Currently, the first cannabis based medicine containing CBD/ 9 -THC combination for the multiple sclerosis related spasticity treatment (Sativex/Nabiximols; GW Pharmaceuticals) has been approved in numerous countries, including Australia, Canada, New Zealand and in most European Union countries (72). Furthermore, a drug composed solely of CBD (Epidiolex; GW Pharmaceuticals) has been approved in June 2018 in the United States for the treatment of Dravet and Lennox-Gastaut syndromes in children (52,73,74).…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…Data obtained from these studies confirmed CBD's anti-seizure properties along with a good tolerance profile. Currently, the first cannabis based medicine containing CBD/ 9 -THC combination for the multiple sclerosis related spasticity treatment (Sativex/Nabiximols; GW Pharmaceuticals) has been approved in numerous countries, including Australia, Canada, New Zealand and in most European Union countries (72). Furthermore, a drug composed solely of CBD (Epidiolex; GW Pharmaceuticals) has been approved in June 2018 in the United States for the treatment of Dravet and Lennox-Gastaut syndromes in children (52,73,74).…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…Multiple sclerosis is a disabling autoimmune disease involving nerve degeneration and currently there are few reliably curative treatments [ 90 ]. Currently, a marijuana based oromucosal spray (Sativex), containing THC:CBD at 1:1 ratio is available as add-on treatment for spasticity among multiple sclerosis patients, supported by several RCTs and reviews [ 91 93 ]. The proposed mechanism of action for Sativex is unclear, though it is thought that CBD and THC synergistically act on non-cannabinoid receptors to exert its therapeutic effects [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis of clinical trials on the use of cannabinoids for spasticity due to MS, da Rovare et al found an insignificant difference related to spasticity between cannabinoids and placebo ( p = 0.18) [ 104 ]. Recently, Akgün et al systematically reviewed publications on the THC:CBD spray use for refractory MS spasticity and found that the proportion of patients reaching the threshold of minimal clinical important (CI) difference, with at least a 20% reduction of the spasticity Numeric Rating Scale score after four weeks ranged from 41.9% to 82.9% [ 105 ]. A current study examines the efficacy of Cannabis in spasticity due to MS ( Table 1 ).…”
Section: The Effects Of Cannabinoid-based Treatments In Different mentioning
confidence: 99%